Determinan Pemeriksaan Triple Eliminasi pada Ibu Hamil di Wilayah Operasional Puskesmas Pagar Dewa dan Puskesmas Kibang Budi Jaya Kabupaten Tulang Bawang Barat - Andhini, Friska; Susianti, Susianti; Pramesona, Bayu Anggileo (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2024)
In Lampung Province, a 100% completion rate for triple elimination exams was the projected goal for 2022. Nevertheless, the collected data shows that the achievement—at 84.1%—is less than the goal. Comparably, the accomplishment rate in Tulang Bawang Barat Regency is at 83.1%. In the Tulang Bawang Barat working region, Kibang Budi Jaya and Pagar Dewa Public Health Center only obtained 62% and 52.4%, respectively. The purpose of this study is to determine the variables that pregnant women in Tulang Bawang Barat Regency's working regions of Pagar Dewa and Kibang Budi Jaya Health Center perceive influence their intention to undergo triple elimination. Cross-sectional design, analytical survey research methodology is used. Proportional random sampling was used to conduct the study in Pagar Dewa and Kibang Budi Jaya Health Center, Tulang Bawang Barat Regency, from September to October 2023. Tests for reliability and validity were carried out using Cronbach's alpha and the Pearson product moment. SPSS was used to perform univariate, bivariate, and multivariate data analysis. According to the findings, pregnant women who are well educated (46%), have a positive attitude (50.7%), have support from family/husband and healthcare professionals (51.5%), and live close to Health Center (51.2%) are more likely to have triple elimination exams. In multivariate analysis, the primary element is the attitudes of the respondents. The report makes recommendations for improving communication campaigns for healthcare providers to encourage increased involvement of pregnant women in triple elimination exams, as well as training in HIV/AIDS, syphilis, and hepatitis B counseling.